An RNA Sequencing Transcriptome Analysis Reveals Novel Insights into Molecular Aspects of the Nitrate Impact on the Nodule Activity of Medicago truncatula . Issue 1 (27th November 2013) - Cabeza, Ricardo; Koester, Beke; Liese, Rebecca; Lingner, Annika; Baumgarten, Vanessa; Dirks, Jan; Salinas-Riester, Gabriela; Pommerenke, Claudia; Dittert, Klaus; Schulze, Joachim
Abstract : A nitrate-induced decline in nitrogenase activity in Medicago truncatula nodules is connected with a strong down-regulation of genes for nodule-specific cysteine-rich peptides and leghemoglobins, changes in inner cell iron allocation, and a decline in nodule respiration efficiency . Abstract: The mechanism through which nitrate reduces the activity of legume nodules is controversial. The objective of the study was to follow Medicago truncatula nodule activity after nitrate provision continuously and to identify molecular mechanisms, which down-regulate the activity of the nodules. Nodule H2 evolution started to decline after about 4 h of nitrate application. At that point in time, a strong shift in nodule gene expression (RNA sequencing) had occurred (1, 120 differentially expressed genes). The most pronounced effect was the down-regulation of 127 genes for nodule-specific cysteine-rich peptides. Various other nodulins were also strongly down-regulated, in particular all the genes for leghemoglobins. In addition, shifts in the expression of genes involved in cellular iron allocation and mitochondrial ATP synthesis were observed. Furthermore, the expression of numerous genes for the formation of proteins and glycoproteins with no obvious function in nodules (e.g. germins, patatin, and thaumatin) was strongly increased. This occurred in conjunction with an up-regulation of genes for proteinase inhibitors, in particular those containing the Kunitz domain. The additionally formed proteins might possibly be involved in reducing nodule oxygen permeability. Between 4 and 28 h of nitrate exposure, a further reduction in nodule activity occurred, and the number of differentially expressed genes almost tripled. In particular, there was a differential expression of genes connected with emerging senescence. It is concluded that nitrate exerts rapid and manifold effects on nitrogenase activity. A certain degree of nitrate tolerance might be achieved when the down-regulatory effect on late nodulins can be alleviated.